Post-occupancy evaluation and codesign in mental healthcare buildings: User’s input as a driver for functional and technical adaptations in post COVID-19 reality - Goulart, Fernanda de Moraes; Ono, Rosaria (Frontiers in Built Environment, 2022)
During the COVID-19 pandemic, social distancing protocols imposed the suspension of many activities in mental healthcare facilities, limiting the use of the facility to people in comprehensive care. With the advancement of vaccination, these buildings are gradually reopening for community use. However, managers and workers now face challenges in accommodating new design demands related to reducing the risk of contamination by COVID-19 within the building. This research adopted a multi-method approach in two phases, combining a post-occupancy evaluation with a cocreation activity to help mental healthcare workers and patients to suggest design changes in their environment. Three Psychosocial Care Centers (CAPS) in São Paulo were selected as case-study buildings. The first phase was the Post-Occupancy Evaluation (POE), in which the lead researcher conducted a walkthrough with the facility administrator, applied questionnaires to 100 employees, and conducted a walking interview with 12 ,patients. During Phase 02, a codesign activity entitled “Dream CAPS” was conducted with 25 healthcare workers and 12 patients. In this activity, participants were asked to customize a physical model of a mental healthcare facility, choosing the wall and floor finishings, the types of openings (windows, doors), furniture, and ornaments. Afterward, they participated in an interview with illustrated cards. All activities were audio-recorded and textual analysis qualified and categorized the content. Objective and subjective data analysis identified five characteristics of the built environment that prevented or increased risk of COVID-19 spread: Places that support risk mitigation procedures, access and circulation control, extended use of outdoor spaces, natural and artificial air renovation systems, and materials resistant to terminal cleaning. Patients participated in the activities but did not express opinions on the impact of architecture on airborne disease prevention. Healthcare workers claimed that environments that improve mental health must be attractive and prone to social interaction and relaxation without compromising biological safety. The combination of post-occupancy evaluation and codesign proved an excellent tool to identify the demands of mental healthcare buildings and discuss the solutions that must be implemented to deal with contemporary and future crises in a pandemic context.